Initial Treatment of Meningocele and Myelomeningocele Lesion in Children - Ammar Anwer; Naveed Ahmad Khan; Obaid Ur Rehman; Javaria Siddiq; Abrar Ullah Khan (Pakistan Journal of Medicine and Dentistry)
Background: Myelomeningocele is a severe form of spina bifida. The disease significantly impacts survival and neurological outcomes in children. The purpose of this study is to investigate the effect of in-time assessment and surgical intervention on functional outcomes in children with MMC.